2000
DOI: 10.1086/308362
|View full text |Cite
|
Sign up to set email alerts
|

Far‐Ultraviolet Absolute Flux of α Virginis

Abstract: We present the far ultraviolet spectrum of α Virginis taken with EURD spectrograph on-board MINISAT-01. The spectral range covered is from ∼ 900 to 1080Å with 5Å spectral resolution. We have fitted Kurucz models to IUE spectra of α Vir and compared the extension of the model to our wavelengths with EURD data. This comparison shows that EURD fluxes are consistent with the prediction of the model within ∼ 20 − 30 %, depending on the reddening assumed. EURD fluxes are consistent with Voyager observations but are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…It has been widely discussed in the literature that deviations from LTE are to be expected for hot stars and the cores of strong lines in stars of intermediate type (Mihalas 1972). However, it has also been demonstrated that at low resolution the agreement between LTE and NLTE model fluxes is good, and that comparison of far-UV and mid-UV observational data with LTE model fluxes also results in good agreement (Morales et al 2000). At high resolution such a comparison has been anticipated by but not yet quantitatively assessed.…”
Section: Lte Vs Nltementioning
confidence: 99%
“…It has been widely discussed in the literature that deviations from LTE are to be expected for hot stars and the cores of strong lines in stars of intermediate type (Mihalas 1972). However, it has also been demonstrated that at low resolution the agreement between LTE and NLTE model fluxes is good, and that comparison of far-UV and mid-UV observational data with LTE model fluxes also results in good agreement (Morales et al 2000). At high resolution such a comparison has been anticipated by but not yet quantitatively assessed.…”
Section: Lte Vs Nltementioning
confidence: 99%
“…Further information regarding the spacecraft mission and the EURD instrument is provided by Edelstein et al [2001] and Gómez et al [2001]. Absolute calibration is discussed by Morales et al [2000, 2001], with in‐flight calibration in the 911–1100 Å wavelength interval based on α Vir (Spica, HD 116658) and other bright B star spectrum measurements. A preliminary description of the nightside airglow as seen by EURD is given by López‐Moreno et al [1998].…”
Section: March 2000 Measurementsmentioning
confidence: 99%
“…The model spectral energy distribution (SED) of Spica for i = 116 • is a pretty good match to archival absolute spectrophotometry ( EURD and IUE data for Spica, HD 116658, 13-color spectrophotometry data for Spica, HR 5056 ) as shown in Figure 4, at least longward of 1100 Å. The model SED is systematically lower the Espectrógrafo Ultravioleta extremo para la Radiación Difusa (EURD) spectrum (Morales et al 2000), suggesting perhaps a weaker far-UV extinction than provided by the (Cardelli et al 1989) mean extinction curve, a cooler primary star and/or an absolute calibration issue with the EURD data. We discuss these possibilities further in Section 6.…”
Section: Stellar Atmosphere Models For the Spica Binarymentioning
confidence: 52%